Motywy mitologiczne w poemacie Lukrecjusza De rerum natura - Krukowska, Sylwia (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2013)
Lucretius makes use of myth in a manner which is far from mere indulgence of poetic fantasy. Already at the beginning of his composition he presents the foundational principle of the whole poem – nature is free from divine authority, and people ought to live happily, liberated from fear of the gods’ anger. This concept is also dominant when the poet mourns the ritual killing of Iphigeneia, as well as when he glorifies the victory of Epicurus over prejudice and traditional belief in the gods. In citing established myths Lucretius inevitably uses a negative strategy, disproving old beliefs, but he also takes a positive approach when creating the image of a new god (as happens when he is dealing with the myth of Hercules). The entire argument which he develops leads to one aim – to demonstrate the superiority of science, according to which nature is free from divine interference and is governed by its own immutable laws.
Keywords: Lukrecjusz; De rerum natura; epikureizm; mity greckie